Using Max-Plus Algebra in The Flow Shop Scheduling - Subiono, Subiono (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
In this paper, it is discussed notion of maxplus algebra and their properties. A model of flow shop production system and analyze the dynamical behavior of the system for scheduling problems are derived by means of max-plus algebra. The solutions of these problems are that the optimal sequence of jobs and the regular scheduling are obtained.